Bouncing back - trauma and the HPA-axis in healthy adults - Klaassens, Ellen Renée (Co-Action Publishing, 2010)
BACKGROUND: Dysregulation of the hypothalamic–pituitary–adrenal (HPA)-axis is thought to underlie stress-related psychiatric disorders such as posttraumatic stress disorder (PTSD). Some studies have reported HPA-axis dysregulation in trauma-exposed (TE) adults in the absence of psychiatric morbidity. In this dissertation we set out to unravel part of the mechanism that underlies the complex relations between trauma exposure, stress regulation, and psychopathology. METHOD: Mentally healthy TE subjects were compared with non-trauma-exposed (NE) healthy controls. To distinguish between the potential effects of childhood trauma and adulthood trauma, we included women exposed to childhood trauma as well as men who were exposed to trauma during adulthood. Basal HPA-axis functioning was assessed with salivary cortisol samples. HPA-axis reactivity was assessed with the dexamethasone/corticotropin-releasing hormone (Dex/CRH) test. RESULTS: The results show that childhood trauma exposure is associated with an attenuated cortisol response after the Dex/CRH challenge test in women. In contrast, trauma exposure during adulthood was not associated with alterations in HPA-axis regulation after the Dex/CRH test. Neither childhood trauma nor adulthood trauma were associated with basal HPA-axis functioning. CONCLUSION: Childhood trauma rather than adulthood trauma may chronically affect HPA-axis functioning. Since the association between adulthood trauma and resilience to psychopathology cannot be explained by HPA-axis functioning alone, other factors must play a role.